Penguatan Ketahanan Keluarga melalui Strategi Integratif di Bidang Kesehatan, Pendidikan, dan Pemberdayaan Ekonomi di Desa Bendung - Andriani, Rina; Damayanti, Ira; Saputra, Desma Yuliadi; Febsi, Yania; Rofika, Rofika; Choerunnisa, Najwa; Karmelia, Arina; Nuramadhan, Aji; Nurul Lintang, Adinda Mutiara; Maulana, Ibnu (Universitas Pahlawan Tuanku Tambusai, 2025)
The counseling activity in Bendung Village aims to improve the community’s quality of life through the integration of public awareness on health, the importance of education within the family, and economic empowerment (SMEs). The program encourages families to adopt a healthy lifestyle, maintain cleanliness, utilize available health services, support their children’s education to foster a smart and independent generation, and strengthen family economic capacity through SMEs, skills development, and innovative marketing strategies. The activity followed four main stages: preparation, implementation, evaluation, and reporting. The counseling was held on August 7, 2025, at the Bendung Village Office with 36 participants, consisting of 29 women and 7 men representing different neighborhood units (RT). The speakers were lecturers and practitioners in related fields, including Yania Febsi, S.Gz., M.K.M., Desma Yuliadi Saputra, M.Pd., and Ira Damayanti, S.T., M.T. The results showed active participation and enthusiasm from the participants during discussions, indicating the high interest of the community. This underscores the importance of an integrative strategy based on collaboration among the community, academics, and village government to achieve family resilience that is healthy, educated, and economically independent.